2002
DOI: 10.1055/s-2002-32318
|View full text |Cite
|
Sign up to set email alerts
|

Underdiagnosis of Sleep Apnea Syndrome in U.S. Communities

Abstract: We hypothesize that clinical recognition rates for obstructive sleep apnea-hypoapnea syndrome (OSAHS) are influenced by comorbidity and demographic factors. Data on medical disorders, symptoms of sleep disorders, and cardiovascular risk factors gathered from 15,699 individuals in the Sleep Heart Health Study were compared. Participants were classified into three groups: those with a self-reported physician diagnosis of OSAHS, those with self-reported physician-diagnosed and -treated OSAHS, and those reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 400 publications
(114 citation statements)
references
References 5 publications
1
107
0
6
Order By: Relevance
“…41 However, Ͼ85% of patients with clinically significant and treatable OSA have never been diagnosed, and referral populations of OSA patients represent only the "tip of the iceberg" of OSA prevalence. 42,43 In addition to emphasizing the large burden of untreated OSA in the general population, the low level of medical detection demands caution in generalizing observations of OSA patients diagnosed in sleep clinics to cardiovascular disease patients with occult OSA. Understanding predictors of OSA free from sleep clinic referral bias is necessary to recognize cardiovascular disease patients likely to have OSA.…”
Section: Central Sleep Apneamentioning
confidence: 99%
“…41 However, Ͼ85% of patients with clinically significant and treatable OSA have never been diagnosed, and referral populations of OSA patients represent only the "tip of the iceberg" of OSA prevalence. 42,43 In addition to emphasizing the large burden of untreated OSA in the general population, the low level of medical detection demands caution in generalizing observations of OSA patients diagnosed in sleep clinics to cardiovascular disease patients with occult OSA. Understanding predictors of OSA free from sleep clinic referral bias is necessary to recognize cardiovascular disease patients likely to have OSA.…”
Section: Central Sleep Apneamentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Community surveys have shown that OSA affects approximately 7% of the middle-aged population, [10][11][12] with as many as 80% of those affected being undiagnosed. [13][14][15] Thus, OSA presents a serious public health concern with respect to road safety.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…In the U.S., obesity and OSA are both on the rise. But only about 20% of OSA is diagnosed, and even a smaller percentage is effectively treated [27][28][29][30]. OSA is a well-known independent risk factor for a variety of diseases related to cardiovascular disease, including hypertension, diabetes, cardiac arrhythmia, stroke, and coronary heart disease [5,8,9,14,31].…”
Section: Discussionmentioning
confidence: 99%